2004
DOI: 10.1007/s00134-004-2439-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of expiratory tracheal gas insufflation in patients with severe head trauma and acute lung injury

Abstract: In patients with severe head trauma and ALI receiving mechanical ventilation, expiratory tracheal gas insufflation allowed the targeted arterial PCO(2) level to be maintained together with a substantial reduction in tidal volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Our data suggest that in addition to a lower PaO 2 /FIO 2 , ventilation with large VTs and relatively high RR represents an important predictor of ALI/ARDS development in patients with severe brain injury. Further studies are required to identify optimal ventilator strategies to protect the lung and maintain a tight a CO 2 control (35).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that in addition to a lower PaO 2 /FIO 2 , ventilation with large VTs and relatively high RR represents an important predictor of ALI/ARDS development in patients with severe brain injury. Further studies are required to identify optimal ventilator strategies to protect the lung and maintain a tight a CO 2 control (35).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that TGI can be used either to decrease PaCO 2 in the setting of hypercapnia or to maintain normocapnia while tidal volume is decreased [66]. In patients with severe head trauma and ALI, Martinez-Perez et al [67] showed that the application of phasic TGI (at mid-to-end expiration) allowed ventilation with lower tidal volumes and driving pressures while maintaining PaCO 2 constant without any deleterious effects on cerebral parameters.…”
Section: Alternative Ventilatory Techniquesmentioning
confidence: 98%
“…Alternative, rescue ventilatory strategies for severe TBI/ARDS patients include prone positioning [5], high-frequency percussive ventilation (HFPV) [5], CMV-TGI [32], pumpless extracorporeal lung assist (pECLA) with a heparin-coated circuit [5,33], and extracorporeal membrane oxygenation (ECMO) [34]. Regarding the use of the first two strategies in TBI/ARDS, only scarce and inconclusive published data exist [5].…”
Section: Discussionmentioning
confidence: 99%